ENVIRONMENTAL AND BIOLOGICAL FEATURES AND ASSESSMENT OF THE CURRENT STATE OF ZYGOPHYLLUM FABAGO L. (ZYGOPHYLLACEAE) POPULATIONS IN THE ILE-BALKHASH REGION (Experimental biology, 2025)
The article explores the ecological and biological characteristics of Zygophyllum fabago L. populations in the Ile-Balkhash region of Almaty Province. It analyzes coenopopulations' current state, morphological traits, life forms, and ecological responses in saline and semi-desert ecosystems. The flora associated with Zygophyllum fabago consists of 71 species from 47 genera and 20 families, dominated by xerophytes (42.25%), mesoxerophytes (28.17%), and mesophytes (14.08%). Key families include Chenopodiaceae (21.13%), Fabaceae (16.90%), and Asteraceae, comprising 60.56% of the flora. The study highlights Z. fabago’s high salt tolerance, its role in soil stabilization, and its use in traditional medicine as an antiseptic, anti-inflammatory, and wound-healing agent. A taxonomic and ecological analysis underscores the uniqueness of the Ile-Balkhash region's ecosystems and the need for conservation to protect this species and its sustainable use.
Keywords: Zygophyllum fabago L.; Zygophyllaceae; coenopopulation; Ile-Balkhash region